Mode-tunable, micro/nanoscale electrohydrodynamic deposition techniques for optoelectronic device fabrication. Issue 37 (9th September 2022) - Duan, Yongqing; Li, Huayang; Yang, Weili; Shao, Zhilong; Wang, Qilu; Huang, YongAn; Yin, Zhouping
Abstract : Electrohydrodynamic deposition is capable of creating thin films by electrospray, micro/nanofibers by electrospinning and micro/nanodroplets by EHD jet printing. This jetting mode tunability presents advantages in optoelectronic devices fabrication. Abstract : The rapid development of fascinating new optoelectronic materials and devices calls for the innovative production of micro/nanostructures in a high-resolution, large-scale, low-cost fashion, preferably compatible with flexible/wearable applications. Powerful electrohydrodynamic (EHD) deposition techniques, which generate micro/nanostructures using high electrical forces, exhibit unique advantages in high printing resolution (<1 μm), tunable printing modes (electrospray for films, electrospinning for fibers and EHD jet printing for dots), and wide material applicability (viscosity 1–10 000 cps), making them attractive in the fabrication of high-density and high-tech optoelectronic devices. This review highlights recent advances related to EHD-deposited optoelectronics, ranging from solar cells, photodetectors, and light-emitting diodes, to transparent electrodes, with detailed descriptions of the EHD-based jetting mechanism, ink formulation requirements and corresponding jetting modes to obtain functional micro/nanostructures. Finally, a brief summary and an outlook on the future perspectives are proposed.